BIM-based prototype of a mathematical model of construction planning - Kontrimovičius, Robertas; Ustinovichius, Leonas (Journal of Civil Engineering and Management, 2023)
This article tackles the problem of rational and effective planning of the entire construction site, including the planning of mechanisms, equipment, warehouse space, temporary buildings, temporary engineering networks, etc. The authors propose the principles of creating a mathematical model to calculate the needs of construction objects, using the photogrammetry model. The problems raised can be solved with the use of BIM in the preparation for construction planning stage. The prototype mathematical model presented in this article addresses these issues: identify current situation, using photogrammetry model, define optimal number and location of construction site objects, avoid conflicts between cranes, detect possible hoisting problem, avoid overload of cranes, and of course construction site planning. Therefore, it becomes possible to perform a multicriteria decision-making analysis. Extensive analysis in the pre-construction stage is often abandoned due to the lack of data on the current situation, difficult calculations of the need for mechanisms, equipment and simply due to the lack of time to analyze all possible rational solutions. The data received from the created mathematical prototype could also be used in further construction stages for planning human and material resources, the project schedule and cost estimate.